ANALYSIS OF CIMAHI CITY TRANSPORT SERVICES“CIMAHI – PARONGPONG ROUTE” - Indah, Mufariza Cahya; Kumala Dewi, Nurlaela; Tuhu Prasetyo, Teguh (Journal of Jabar Economic Society Networking Forum, 2024)
This research aims to analyze the level of service satisfaction, attributes that are priority improvements as well as suggestions that can be implemented to increase satisfaction with the service received by passengers. The research was conducted on city transportation on the Cimahi - Parongpong route. The population in this study are passengers who use services on the Cimahi - Parongpong city transportation route where the population in the study is unknown. The sample in this study was selected using the Simple Random Sampling method, namely random users of city transportation services on the Cimahi - Parongpong route, totaling 384 respondents. In this research, data analysis uses the Service Quality (ServQual) and Important Performance Analysis (IPA) approaches. The results of the research show that: the level of satisfaction with city transportation services on the Cimahi - Parongpong route is not 100% in line with passengers' expectations, where the results obtained are 29%, there are still passengers who feel that the service they receive is not satisfactory. Apart from that, the attributes included in the main priorities that need to be improved and the proposals offered are also integrated into service quality and passenger satisfaction in this research.